2019
DOI: 10.1186/s13000-019-0779-3
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinal follicular dendritic cell sarcoma: a rare, potentially under-recognized, and often misdiagnosed disease

Abstract: BackgroundMediastinal follicular dendritic cell sarcoma (FDCS) is extremely rare. Due to potential under-recognization of this disease, it happens to be misdiagnosed, especially on core needle biopsy. We report 3 cases of mediastinal FDCS and provide a literature review to improve better understanding of the tumor and to reduce misdiagnosis.MethodsThree cases of mediastinal FDCS in our clinic practice were studied, including their core needle biopsy and resected specimens, and those cases reported previously i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…Most notably, this FDCS case demonstrates a spectrum of morphologies. The histomorphology of FDCS is usually heterogeneous and has been known to show epithelioid or pleomorphic tumor cells [5–8], myxoid stroma [9, 10], osteoclastic giant cells [11, 12], and CHL-like features [6, 13], among others. However, in this case, the four atypical histopathologic morphologies were all present within the same tumor, which has not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most notably, this FDCS case demonstrates a spectrum of morphologies. The histomorphology of FDCS is usually heterogeneous and has been known to show epithelioid or pleomorphic tumor cells [5–8], myxoid stroma [9, 10], osteoclastic giant cells [11, 12], and CHL-like features [6, 13], among others. However, in this case, the four atypical histopathologic morphologies were all present within the same tumor, which has not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…The first preoperative biopsy may have involved the resection of just the lymph node containing invasive epithelioid cell nests, which resulted in the initial misdiagnosis. The areas similar to ALCL or CHL but that were CD30-positive by IHC (it has been reported that a few FDCS could express CD30 [6, 13]) are another point of diagnostic importance. The treatment of FDCS is typically surgical resection, whereas lymphoma is treated with chemotherapy and radiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histiocytic neoplasms are a type of tumor that arise from the monocyte-macrophage system, including dendritic cells (DCs), macrophages and sometimes histiocytes ( 1 , 2 ). DC tumors are associated with certain types of antigen-presenting cells ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…FDCS consists of a neoplastic proliferation of spindled to ovoid cells exhibiting morphological and immunophenotypic features of FDCs ( 1 ). Misdiagnosis occurs frequently, due to the fact that it has the same micromorphology as other common neoplasms, such as other types of sarcoma and lymphoma ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%